The Vital Human Difference - McFeely, Richard H. (Tufts Archival Research Center, 2006)
Richard McFeely describes how an attack of infantile paralysis (polio) shattered his dreams of a career in physical education, and how his mother's encouragement helped him discover that life was worth living, even in misfortune. This episode is a rebroadcast of an earlier airing.